An Expansible Aortic Ring in Aortic Root Remodeling: Exact Position, Pulsatility, Effectiveness, and Stability in Three-Dimensional CT Study - Holubec, Tomas; Higashigaito, Kai; Belobradek, Zdenek; Dergel, Martin; Harrer, Jan; Alkadhi, Hatem; Zacek, Pavel; Vojacek, Jan (The Annals of thoracic surgery, 2017)
BACKGROUND: The aim of this study was to assess effectiveness, stability, position, and expansibility of an expansible aortic annuloplasty ring with computed tomography (CT). METHODS: Ten men (median age 51 years) scheduled for aortic root remodeling with implantation of external annuloplasty ring underwent contrast-enhanced CT of the aortic root preoperatively, postoperatively, and at a median of 21 months after operation. A reconstructed transverse double oblique view of the aortic base (AB) and of the new defined annuloplasty ring base (ARB; plane of the lower edge of the ring) in systole and diastole were obtained. The diameters, perimeter, and area were measured. In addition, the distances between AB and ARB in the nadir of each sinus were measured. RESULTS: We found 12% reduction of the postoperative AB and 19% of ARB perimeter in both systole (p = 0.004, p < 0.001, respectively) and diastole (p = 0.001, p < 0.001, respectively) compared with preoperative. There was 22% reduction of the postoperative AB area in systole and 24% in diastole (p = 0.002, p = 0.001, respectively) and 33% reduction of the ARB area in systole and 32% in diastole (p < 0.001 for both) compared with the preoperative period. Nearly all measured variables in the follow-up period showed a slight increase compared with the postoperative period; however, they did not reach statistical significance. The postoperative systolic-diastolic differences in the three measured variables at the level of AB and ARB were statistically significant and were maintained throughout the follow-up period. The base of the ring was implanted 2 ± 2 mm at the right, 0 ± 1 mm at the left above the AB, and 2 (-3 to 2) mm at the noncoronary nadir below the AB. CONCLUSIONS: This study demonstrates imaging evidence of the effectiveness, stability, and pulsatility of the annuloplasty ring in aortic root remodeling in follow-up and describes the exact position of the ring at the base of the aortic root.
Keywords: dospělí; Cardiac Valve Annuloplasty; Female; Aorta, Thoracic; Prosthesis Design; aortální chlopeň; anuloplastika srdeční chlopně; zobrazování trojrozměrné; Imaging, Three-Dimensional; Adult; Prostheses and Implants; protézy - design; ženské pohlaví; Tomography, X-Ray Computed; Time Factors; časové faktory; funkce levé komory srdeční; lidé; aortální insuficience; Aortic Valve Insufficiency; následné studie; Humans; retrospektivní studie; Follow-Up Studies; Male; Aged; aorta thoracica; Aortic Valve; lidé středního věku; protézy a implantáty; senioři; mužské pohlaví; Retrospective Studies; Middle Aged; Ventricular Function, Left; počítačová rentgenová tomografie